2022
DOI: 10.3389/fpsyg.2022.920125
|View full text |Cite
|
Sign up to set email alerts
|

Fear, depression, and well-being during COVID-19 in German and South African students: A cross-cultural comparison

Abstract: Various studies have shown a decrease in well-being and an increase in mental health problems during the COVID-19 pandemic; however, only a few studies have explored fear, depression, and well-being cross-culturally during this time. Accordingly, we present the results of a cross-cultural study that (1) compares these mental health scores for German and South African students, (2) compares the correlations among them, and (3) identifies COVID-19 fear, well-being, and depression predictors. German and South Afr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 65 publications
1
4
0
Order By: Relevance
“…The same was found in studies from Lithuania [ 41 ], Austria [ 54 , 55 ] and the Netherlands [ 56 ] (which all found lower WHO-5 scores in females compared to males). In addition, Jusienė et al [ 41 ] and Holm-Hadulla et al [ 57 ] found that females were more likely to report emotional and behavioural problems lasting longer than one year and had more COVID-19 anxiety, suggesting poorer mental health than males, and further supporting our findings. It has been suggested that the explanation for the poorer mental health in female adolescents may be related to COVID-19 restrictions.…”
Section: Discussionsupporting
confidence: 90%
“…The same was found in studies from Lithuania [ 41 ], Austria [ 54 , 55 ] and the Netherlands [ 56 ] (which all found lower WHO-5 scores in females compared to males). In addition, Jusienė et al [ 41 ] and Holm-Hadulla et al [ 57 ] found that females were more likely to report emotional and behavioural problems lasting longer than one year and had more COVID-19 anxiety, suggesting poorer mental health than males, and further supporting our findings. It has been suggested that the explanation for the poorer mental health in female adolescents may be related to COVID-19 restrictions.…”
Section: Discussionsupporting
confidence: 90%
“…Despite limitations, the fndings of this study have substantial implications for public health, particularly in terms of COVID-19 prevention and students' well-being in universities [88]. Many universities in China, Korea, and other countries have conducted back-to-campus studies.…”
Section: Discussionmentioning
confidence: 95%
“…It can be discussed if females suffered more from COVID-19 measures. Cross-cultural research found that females were more likely to report emotional and behavioural problems lasting longer than one year and had more COVID-19 anxiety, suggesting poorer mental health than males (50,51). There is evidence that girls are more likely than boys to rely on their social networks for support when dealing with signi cant life stressors (52).…”
Section: Discussionmentioning
confidence: 99%